DAMPAK NEGATIF BERMAIN GAME DAN MENONTON TAYANGAN BERMUATAN KEKERASAN PADA ANAK (PENYULUHAN PADA SISWA SDN 06 PASAR MUARA LABUH, KAB. SOLOK SELATAN) - M.Kom, Hariyadi, S.Kom (LPPM Universitas Muhammadiyah Sumatera Barat, 2016)
This community service was motivated by the condition in which there a lot of game and TV program containing violence consumed by children. In a city like Muara Labuh, most parents do not have enough time to keep watching and accompany the children neither when playing the game nor watching TV. In addition, the children now have an easy access to play any game. The aim of this project is to deliver the knowledge to the children about the impact of violent contents in TV program and game. The method used in this activity was a talk show including showing the example of proper program for the children as well as the improper one, then it was comprehended by discussion session between the participants and the presenters. After this activity had been conducted, the result showed that the average knowledge of the participants was in maximum value, 2 (after rounded up) which means there is 47% increase in the knowledge on the impact of violent contents in TV program and game. This result is expected to become a foundation for the participants to control the media they consumed without fully depending on parents‟ guidance and control. Key words: Media lite racy, media effect, violence, children